INTERNATIONAL LEGAL FRAMEWORK FOR ENSURING SECURITY OF PROPERTY RIGHTS - Avdeevich Avdeev, Vadim; Anatolievna Avdeeva, Olga; Vsevolodovna Varmund, Ph. D. Victoria Vsevolodovna Varmund; Nikolaevna Bogdanova, Julija; Anatolievna Renglikh, Karina; Vladimirovna Efimova, Olga (Revista Inclusiones, 2020)
The article investigates the international legal principles for ensuring the security of property rights in the conditions of the globalization of modern legal systems. Inviolability of property rights declared by the international community has received different assessments in national legal systems. Inviolability of property rights provides for the use of various state and legal mechanisms to ensure its security. New directions of social and economic development in the conditions of globalization make it necessary to improve the national system in order to ensure security of property rights of individuals and legal entities taking into account international legal principles. Attention is focused on the state of property security declared by international and national law guaranteed by the state. International normative and legal acts aimed at strategic directions of ensuring property security are subject to analysis. The development and implementation by the international community of legal postulates which can be used as a basis for legal regulation of property security in national legal systems is of fundamental importance.